FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA DI KELURAHAN KAPUAS KANAN HULU WILAYAH KERJA PUSKESMAS SUNGAI DURIAN KABUPATEN SINTANG - Juliansyah, Elvi (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2020)
Chronic stunting or malnutrition refers to the form of growth failure. The short and the very short size of one’s body indicate nutritional status based on the body length index by age (PB / U) or the body height index by age (TB / U) which is synonymous to the terms stunted (short) and severely stunted (very short). There were 45 toddlers who suffered stunting in Kelurahan Kapuas Kanan Hulu Sintang Regency in 2018.. The purpose of this study was to determine the determinants of stunting in children under five in Kapuas Kanan Hulu Kelurahan, Sintang District. It was a quantitative study with a case control approach. The population in this study were 438 toddler mothers with a sample of 44 toddler mothers. The data were collected through a questionnaire-based interview. The present research found out that statistically there was a relationship between stunting events and the knowledge (p = 0.010), the attitude (p = 0.010), the practice (p = 0.019), the education (p = 0.019), the work (p = 0.009), and the family income (p = 0.049). It is recommended that the District Health Office and Sungai Durian Community Health Centre intervene with health promotion programs to increase knowledge, improve attitudes, and practices (actions) and work together with related institutions to improve family income. Keywords: Stunting, Risk Factors, and Toddler.